The Influence of Organizational Culture in Subject Teacher Consultation Forums and School Leadership on Physical Education Teachers’ Performance - Tutik Nurrokhim; Suyanto Suyanto; A Faizin (Actual Insight, 2026)
Organizational culture and school leadership are widely recognized as important factors influencing teacher performance and the quality of educational services. A supportive organizational culture encourages collaboration, professional growth, and positive attitudes among teachers, while effective school leadership plays a strategic role in guiding and motivating teachers to achieve institutional goals. This study aims to examine the influence of organizational culture in Subject Teacher Consultation Forums and principal leadership on the performance of Physical Education teachers in state senior high schools in Tuban Regency, Indonesia. This research employed a quantitative approach with an associative research design. The population consisted of 43 Physical Education teachers from 20 state senior high schools, all of whom were included as research participants using a total sampling technique. Data were collected through a structured questionnaire using a five-point Likert scale to measure organizational culture, principal leadership, and teacher performance. The collected data were analyzed using descriptive statistics and regression analysis with the assistance of SPSS version 26. The findings are expected to provide empirical evidence regarding the role of professional organizational culture and school leadership in enhancing teacher performance. The results of this study may contribute to improving teacher professional development and strengthening collaborative learning communities within schools.